THE EFFECT OF JOB MOTIVATION AND JOB DISCIPLINE UPON JOB PERFORMANCE OF EMPLOYEES IN THE PERSONAL CARE DEPARTMENT AT PT. RECKITT BENCKISER INDONESIA - Andi Suwandi; M. Husaen Syaefudin (STIE Binaniaga, 2018)
In this case, the company must be able to manage the existing human resources effectively and efficiently, so the company can achieve the goals that have been set-up. So, employee’s job performance has been a very important role to the success or failure of a company. Several factors that affect employee job performance are motivation and work discipline. Partial test results (T-test) about the influence of motivation on employee’ job performance has shown the value of T-count of 6.146 with significance of 0.000. It indicates that the variable of motivation has positive and significant effect on employee job performance. Because value T-count > T-table or 6.146 > 1.665 and level of significance < level significance or 0.000 < 0.050. and test result regarding the influence of work discipline on employee job performance shows the value of T-count of 3.019 with significance of 0.003. it indicates that the variable of work discipline have positive and significant effect on employee job performance. Because value T-count > T-table or 3.019 > 1,665 and level of significance < level of significance or 0.003 < 0,050.While testing simultaneously (F-test) about the influence of motivation and work discipline on employee job performance shows the value of Fcount of 47,215 with significant of 0,000. It indicates that the variable of motivation and work discipline have positive and significant effect on employee job performance. Because value F-count > F-table or 47,215 > 3,111 and level of significance < level of significance or 0,000 < 0,050.Keywords: Job Satisfaction, Leadership Behavior, Motivation, Performance